Transforming Growth Factor Beta Regulates Proliferation and Invasion of Rat Placental Cell Lines(1) - Lafontaine, Lyne (Biol Reprod, 2011)
Implantation of an embryo in the endometrium is a critical step for continuation of pregnancy, and implantation failure is a major cause of infertility. In rats, the implantation process involves invasion of the endometrial epithelial lining by the trophoblastic cells in order to reach the underlying stromal cells. Transforming growth factor beta (TGFB) is a multifunctional cytokine that regulates proliferation, differentiation, and invasiveness of multiple cell lineages. We used rat HRP-1 and RCHO-1 placental cell lines to perform this study. HRP-1 cells were derived from midgestation chorioallantoic placental explants of the outbred Holtzman rat, whereas RCHO-1 cells were established from a rat choriocarcinoma. MTT proliferation assays revealed that each TGFB isoform decreased HRP-1 cell growth in a dose-dependent manner, whereas RCHO-1 cells were resistant to the growth-suppressive effect of TGFB1 and TGFB3. Only TGFB2 reduced RCHO-1 cell proliferation. Activation of ERK, MAPK14 (p38 MAPK), or SMAD pathways is known to play a role in cell proliferation, and we found that TGFB activates these pathways in both HRP-1 and RCHO-1 cells in an isoform-specific manner. MTT proliferation assays revealed that ERK pathway is partially implicated in TGFB3-reduced HRP-1 cell proliferation. Hoechst nuclear staining and caspase-3 cleavage demonstrated that TGFB isoforms failed to induce apoptosis in both cell lines. Matrigel invasion assays showed that both HRP-1 and RCHO-1 cells exhibit intrinsic invasive ability under untreated conditions. The capacity of HRP-1 cells to invade the Matrigel was selectively increased by TGFB2 and TGFB3, whereas all TGFB isoforms could increase the invasiveness of RCHO-1 cells. These important functional studies progressively reveal a key role for TGFB in regulating proliferation and invasiveness of placental cells.